Ethically Deployed Defaults: Transparency and Consumer Protection through Disclosure and Preference Articulation. (October 2016) - Steffel, Mary; Williams, Elanor F.; Pogacar, Ruth
Defaults are extremely effective at covertly guiding choices, which raises concerns about how to employ them ethically and responsibly. Consumer advocates have proposed that disclosing how defaults are intended to influence choices could help protect consumers from being unknowingly manipulated. This research shows that consumers appreciate transparency, but disclosure does not make defaults less influential. Seven experiments demonstrate that disclosure alters how fair consumers perceive defaults to be but does not attenuate default effects because consumers do not understand how to counter the processes by which defaults bias their judgment. Given that defaults lead consumers to focus disproportionately on reasons to choose the default even with disclosure, debiasing default effects requires that consumers engage in a more balanced consideration of the default and its alternative. Encouraging people to articulate their preferences for the default or its alternative, as in a forced choice, shifts the focus away from the default and reduces default effects.